Ethical Issues in Marketing : A New Dimension and Challenge - Dash, C.K.; Priya, Ashutosh (Indian Journal of Marketing, 2004)
Human values are ethics which are likely to become a matter of serious concern in the emerging scenario of professional management in India and else where because the managerial behaviour shows an escalating degradation of the general accepted norms of business ethics in terms of moral standard. We witness or observe about growing preoccupation with self-interest, which implies lust for wealth, power and recognition. Perhaps the saying ’nothing succeeds like success’ can be presented as the golden rule of the moral order of the modern organization.Management by materialism today is the hand -maid of profit making at any cost. We have no human touch in management; we have lost all human values. Manager and leader in any branch of human enterprise unfortunately are setting a bad example today before the people. The mangers at all level are expected to have a strong and noble character based on basic human values. They must adopt means and ends or objectives based on ethical and moral values. But we have almost the reverse picture in our country and abroad. As a result workers are dehumanized and demoralized.